Re-evaluation of histological diagnoses of malignant mesothelioma by immunohistochemistry - Willén Helena; Kjærheim Kristina; Røe Oluf D; Sandeck Helmut P; Larsson Erik (BMC, 2010)
Abstract Background In order to provide reliable tissue material for malignant mesothelioma (MM) studies, we re-evaluated biopsies and autopsy material from 61 patients with a diagnosis of MM from the period of 1980-2002. Methods Basic positive (Calretinin, EMA, Podoplanin, Mesothelin) and negative (CEA, Ber-Ep4) immunohistochemical (IHC) marker reactions were determined. If needed, more markers were used. Histological diagnoses were made by three pathologists. Survival data were calculated. Results 49 cases (80%) were considered being MM by a high degree of likelihood, five more cases possible MM. Of the remaining seven cases, three were diagnosed as adenocarcinoma, three as pleomorphic lung carcinoma, in one peritoneal case a clear entity diagnosis could not be given. One of the possible MM cases and two of the lung carcinoma cases had this already as primary diagnoses, but were registered as MM. With a sensitivity of 100%, Calretinin and CEA were the most reliable single markers. The amount of MM cells with positive immunoreactivity (IR) for Podoplanin and Mesothelin showed most reliable inverse relation to the degree of atypia. In the confirmed MM cases, there had been applied either no IHC or between one and 18 markers. The cases not confirmed by us had either lacked IHC (n = 1), non-specific markers were used (n = 4), IR was different (n = 1), or specific markers had not shown positive IR in the right part of the tumour cells (n = 3). 46 of the 49 confirmed and three of the not confirmed cases had been diagnosed by us as most likely MM before IHC was carried out. Conclusions In order to use archival tissue material with an earlier MM diagnosis for studies, histopathological re-evaluation is important. In possible sarcomatous MM cases without any positive IR for positive MM markers, radiology and clinical picture are essential parts of diagnostics. IHC based on a panel of two positive and two negative MM markers has to be adapted to the differential diagnostic needs in each single case. New diagnostic tools and techniques are desirable for cases where IHC and other established methods cannot provide a clear entity diagnosis, and in order to improve MM treatment.